Telehealth or in-person HIV care? Qualitative study findings on decision-making from people with HIV and HIV care providers in South Carolina during the COVID-19 pandemic. - Valerie Yelverton; Salome-Joelle Gass; Daniel Amoatika; Christopher Cooke; Jan Ostermann; Nabil Natafgi; Nicole L Hair; Bankole Olatosi; Otis L Owens; Shan Qiao; Xiaoming Li; Caroline Derrick; et al. (PLOS Digital Health)
The COVID-19 pandemic disrupted HIV care services across the United States. Telehealth was rapidly implemented to ensure HIV care continuity. Despite the evidence of unequal telehealth uptake among some people with HIV (PWH), the decision-making processes to determine who received telehealth or in-person care are under-researched. This study assessed which decision criteria and processes determined which HIV care visit type was used by PWH and HIV care providers during the COVID-19 pandemic. Qualitative in-depth interviews with 18 PWH and 10 HIV care providers from South Carolina assessed PWHs' and HIV care providers' decision-making criteria and processes for telehealth HIV care during the COVID-19 pandemic. Interviews were analyzed using thematic analysis. Most PWH (11 out of 18) and all providers had used telehealth for HIV care. To guide visit type decisions, interviewees reported decision-making criteria across four domains: patient-related criteria, clinical criteria, provider preference, and HIV care continuity. Patient-related criteria included patient preference, convenience, fear of COVID-19 exposure and stigma, and transportation barriers. Clinical criteria included the need for a physical exam, a person's care history and health status. While all identified decision criteria were important, we found a hierarchical structure: care continuity superseded other criteria. Some clinical criteria were reported as decision-relevant criteria by providers but not PWH. Most PWH reported that they were included or took the lead in the visit type decision process. Decision-making processes to determine PWHs' HIV care visit types considered criteria across multiple domains. The superseding criteria was to sustain HIV care continuity. To guide future telehealth use, shared decision-making is needed to weigh patient-related, provider-related, and clinical decision criteria and maintain care continuity, and to comprehensively include all relevant decision criteria.